The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/w9100749
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic of Dalinor Lakes in the Inner Mongolian Plateau and Its Driving Factors during 1976–2015

Abstract: Climate change and increasing human activities have induced lake expansion or shrinkage, posing a serious threat to the ecological security on the Inner Mongolian Plateau, China. However, the pattern of lake changes and how it responds to climate change and revegetation have rarely been reported. We investigated the pattern of lake-area changes in the Dalinor National Nature Reserve (DNR) using Landsat imagery during 1976-2015, and examined its relationship with changes in climate and vegetation factors. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Changes in climate elements, including an increase in air temperature, transform and accelerate both the water cycle and changes in the structure of water balance in river or lake catchments [30,[55][56][57]. The rapid decrease in the surface area of Rakutowskie Lake is probably a result of the observed increase in evaporation and periodically smaller precipitation ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in climate elements, including an increase in air temperature, transform and accelerate both the water cycle and changes in the structure of water balance in river or lake catchments [30,[55][56][57]. The rapid decrease in the surface area of Rakutowskie Lake is probably a result of the observed increase in evaporation and periodically smaller precipitation ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the new institutional arrangements (fencing and grazing exclusion), stock rating decreased significantly after 2000, which had a significantly positive effect on vegetation conditions (Huang et al, 2009), but a negative effect on herders' livelihoods (increases in the cost of livestock production and decreases in the net income of herders; Uthes, Li, Zhen, & Cao, 2010). Li, Gao, Li, Yan, & Xu, 2017;Tao et al, 2015). Previous research showed that degraded grassland can recover under grazing ban conditions (Jiang, Han, & Wu, 2006).…”
Section: Policy Framementioning
confidence: 99%
“…Data from remote sensing satellites, such as Landsat, MODIS, Sentinel-1, CBERS-1, and so on [9][10][11][12], has been widely used for mapping surface water. Landsat datasets are likely the most common data employed to identify the water surface because of their high spatial resolution, free availability, and their long sequence feature [10,13]. Han et al [11] used Landsat data to study changes in the winter wetlands of Poyang Lake from 1973 to 2013.…”
Section: Introductionmentioning
confidence: 99%